Patrimônio em festa :etnografia, documento e registro da Festa dos Homens Pretos da Santa de Chapada do Norte - Roberto de Moura Fonseca (2010)
Once upon a time a Party of the Virgin of the Rosary of the Blacks Men of Chapada do Norte, which invited the Heritage of Minas Gerais as an accomplice of its preservation. Once upon a time the Heritage of Minas Gerais who wanted to preserve a Party of Virgin of the Rosary of the Blacks of Chapada do Norte and did not know how. Once upon a time a Tourist Anthropologist who was trapped in a maze for the Party and the Heritage. So, this is the history, the document and the ethnography to how the Party has seduced the Heritage and Tourist Anthropologist, how the Heritage preserved the Party and how the Tourist Anthropologist walked through the maze.